Desarrollo de materiales modificadores de propiedades eléctricas de los elementos aislantes poliméricos vinílicos basados en tecnologías de Nanoescala. (2021)
The main objective of this research work was to evaluate the impact of the synthesized additives, through nanotechnology, in the electrical properties of the PVC to improve its insulator behavior in order to obtain a plastic coating that withstand long exposure times to unfavorable environments. Modified nanoparticles were synthesized using surface engineering with silica, aluminum and magnesium-base compounds along with organic acids and evaluated in an insulating coating formula for electrical cables with an operating temperature of 105 °C. In the experimental research, the nanoadditive was added to the thermal stabilizer used in the manufacturing of PVC compound and the nanoadditive concentration was posed taking into account the economic and performance impact on the final product, seeking for an increase below 0.3 USD per kilogram in the thermal stabilizer cost. The compound was used to manufacture flat PVC plates used for the performance and accelerated aging tests. Properties like color, hardness and volume resistivity before and after water absorption were evaluated. Finally, there were 3 successful prototypes obtained along with its economical analysis and its impact on the stabilizer cost and a proposal for the implementation of the process at an industrial level in Carboquimica.